Synchronization in a coupled two-layer quasigeostrophic model of baroclinic instability - Part 1: Master-slave configuration - Castrejón-Pita, A; P. L. Read (Copernicus Publications, 2009)
Synchronization is studied using a pair of diffusively-coupled, two-layer quasi-geostrophic systems each comprising a single baroclinic wave and a zonal flow. In particular, the coupling between the systems is in the well-known master-slave or one-way configuration. Non-linear time series analysis, phase dynamics, and bifurcation diagrams are used to study the dynamics of the coupled system. Phase synchronization, imperfect synchronization (phase slips), or complete synchronization are found, depending upon the strength of coupling, when the systems are either in a periodic or a chaotic regime. The results of investigations when the dynamics of each system are in different regimes are also presented. These results also show evidence of phase synchronization and signs of chaos control.